Sexual Dimorphism and Gender in Infectious Diseases - Gay, Laetitia; Melenotte, Cléa; Lakbar, Ines; Mezouar, Soraya; Devaux, Christian; Raoult, Didier; Bendiane, Marc-Karim; Leone, Marc; Mège, Jean-Louis (Frontiers in Immunology, 2021)
Epidemiological studies and clinical observations show evidence of sexual dimorphism in infectious diseases. Women are at less risk than men when it comes to developing most infectious diseases. However, understanding these observations requires a gender approach that takes into account an analysis of both biological and social factors. The host’s response to infection differs in males and females because sex differences have an impact on hormonal and chromosomal control of immunity. Estradiol appears to confer protective immunity, while progesterone and testosterone suppress anti-infectious responses. In addition, genetic factors, including those associated with sex chromosomes, also affect susceptibility to infections. Finally, differences in occupational activities, lifestyle, and comorbidities play major roles in exposure to pathogens and management of diseases. Hence, considering sexual dimorphism as a critical variable for infectious diseases should be one of the steps taken toward developing personalized therapeutic approaches.